Child labour in Fostering Practices: A study of Surulere Local Government Area lagos State, Nigeria (2010)
Many studies in Nigeria have been carried out to examine the trend and outcome of fostering practices and child labour independently but such have generally overlooked the issue of child labour in fostering practices. The study therefore, attempts to examine the existence of child labour in fostering practices: through a combination of quantitative and qualitative research methods, the study exposes how children are being used as economic support by foster parents and the exploitation of the socialization process which sees research as part of the upbringing of a child. This is explicated through the increasing level of poverty in cities and rural areas which have necessitated the act of child labour in fostering practices. Major findings from the study revealed that child labour is on the increase and the effects were negative on the children. Findings were linked to the downturn of the economy which prompted child labour as a coping strategy. Among the sampled respondents, the effect of the economic activities on their education was negative. The need for househelp, economic crises and schooling were major reasons sustaining fostering practices vis-a-vis child labour. Biological parents influence had minimal effect on foster parents control over the economic activities they engaged the foster children which was also observed to be gender based. On the whole, child labour was viewed as important irrespective of the menance of child labour. Based on these findings, the study suggested that there is need for government as well as civil society groups' intervention to alleviate the problem of child labour in fostering practices.